Silanized silica compatibilization of NBR/gelatin blends for the production of green rubber products. (August 2019) - Gill, Yasir Qayyum; Irfan, Muhammad Shafiq; Saeed, Farhan; Nadeem, Muhammad; Ehsan, Hira
In this study, acrylonitrile butadiene rubber (NBR)–gelatin blends were prepared by conventional melt blending process at 40°C processing temperature and 50 r min −1 rotor speed in a Brabender-Plasticorder. Gelatin loading was varied from 10 to 50 phr. The extent of reinforcement was more prominent at 30 phr gelatin loading without compatibilization. Up to 30 phr gelatin loading, the tensile strength, abrasion resistance, and morphological properties of blends increased. After 30 phr gelatin loading, the toughness and abrasion resistance declined for samples containing 40 and 50 phr gelatin. However, cross-link density and hardness kept on increasing beyond 30 phr loading. At optimum loading of 30 phr of gelatin, 3, 3.5, and 4 phr of nano-silanized silica was added as a compatibilizer for further improvement in properties. After compatibilization of 30 phr gelatin sample with 4 phr of nano-silanized silica, the extent of reinforcement in terms of tensile strength was improved from 8.97 to 9.92 MPa.